2020
DOI: 10.1111/cea.13730
|View full text |Cite
|
Sign up to set email alerts
|

Detection of specific IgE against linear epitopes from Gal d 1 has additional value in diagnosing hen’s egg allergy in adults

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Some of the peptides identified in these studies have been reported to be useful to assess the epitope-recognition profiles of antibody repertoires for different isotypes [ 60 , 61 ], for diagnosis [ 52 •, 55 , 62 •, 63 ] or to stratify patients regarding sensitivity to challenge and outcome of oral immunotherapy [ 51 , 64 •, 65 ]. Machine learning algorithms combining epitope and antigen-specific IgE levels in the first 2 to 3 years of life improved the accuracy of predicting peanut allergy at age 4 + years [ 66 ].…”
Section: Advantage Of Human Ige Monoclonal Antibodies For Epitope Map...mentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the peptides identified in these studies have been reported to be useful to assess the epitope-recognition profiles of antibody repertoires for different isotypes [ 60 , 61 ], for diagnosis [ 52 •, 55 , 62 •, 63 ] or to stratify patients regarding sensitivity to challenge and outcome of oral immunotherapy [ 51 , 64 •, 65 ]. Machine learning algorithms combining epitope and antigen-specific IgE levels in the first 2 to 3 years of life improved the accuracy of predicting peanut allergy at age 4 + years [ 66 ].…”
Section: Advantage Of Human Ige Monoclonal Antibodies For Epitope Map...mentioning
confidence: 99%
“…While linear epitopes are common in food allergens due to their processing in the digestive tract and/or before ingestion (e.g., thermal treatment), conformational or discontinuous epitopes also exist in foods [ 50 , 63 ], and are the most common epitopes in inhalant allergens. Conformational epitopes involve amino acids that are non-contiguous in the amino acid sequence but are close in the space due to the protein folding.…”
Section: Advantage Of Human Ige Monoclonal Antibodies For Epitope Map...mentioning
confidence: 99%
“…These results also provide preliminary basic research for the design of epitope vaccine and preparation of monoclonal antibody with highly conserved peptide epitopes ( 31 ). Similarly, Anna et al found that linear epitopes were important for allergen identification through SDS-PAGE and WB under denaturing conditions ( 32 ). Wang et al also found that two highly conserved linear epitopes of Hexon Protein could help design new structure-based epitope vaccines or therapeutic vaccines ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…This coincided with a number of studies evaluating the burden of peanut allergy and calling for improved protection for people with food allergy 69‐71 . Investigation of component IgE as a marker for ingestion, an immunological target and a discriminator with added diagnostic value also continues to be a busy area of science 72‐79 . Characteristics of infant food anaphylaxis were defined in one of the most extensive published series—hives, hypotonia and hypotension were common features in a French series with 61 infant cases, compared with 386 cases in preschool children 80 .…”
Section: Food Allergymentioning
confidence: 98%